OPINION WRITING ABILITY USING THE WORK TOURISM METHOD OF GRADE XI STUDENTS OF STATE HIGH SCHOOL 2 TERNATE - Suhardi Kasim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the improvement of students' opinion writing skills of grade XI SMA Negeri 2 Ternate through the application of the field trip method. The background of this study is the low ability of students in writing opinions caused by the lack of direct experience and limited ideas in developing arguments logically and systematically. The method used in this study is classroom action research (CAR) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 30 grade XI students. The instruments used included observation sheets, interview guidelines, and opinion writing ability tests. The results of the study showed that the field trip method can significantly improve students' opinion writing skills. This can be seen from the increase in students' average scores in each cycle. In cycle I, the average score of students reached 70, while in cycle II it increased to 82. Thus, it can be concluded that the field trip method is effective in improving students' opinion writing skills of grade XI SMA Negeri 2 Ternate.